Social and economic returns of wellness (2004)
Wellness, as defined by Donatelle and Davis, refers to the "dynamic, ever changing process of trying to achieve one's individual potential in each of several interrelated dimensions, namely, physical health, social health, mental health, environmental health, and spiritual health." This year's NDAP convention had adopted as a focus "Total Wellness" in recognition of the fact that development of all the facilities is the key to the attainment of a productive and quality life. In the early years, the goal of adequate nutrition has dwelt largely on its significant impact on physical health or prevention of illness, with little reference to the tremendous consequences or interrelationships it has on the realization of the other aspects of the well-being of an individual, more specifically, the mental, emotional, and social development of the biosocial organism. This paper will attempt to review some empirical evidences on why investment in nutrition makes a sound investment in a productive, mentally capable, emotionally stable, and socially adjusted human being, one who is "in unity with the environment and guided by a sense of value in life".
Keywords: Nutrition; Physical fitness; health and wellness